Progressive resistance training in cachectic head and neck cancer patients undergoing radiotherapy: a randomized controlled pilot feasibility trial - Manuel Grote; Cornelius Maihöfer; Martin Weigl; Patricia Davies-Knorr; Claus Belka (Radiation Oncology, 2018)
Abstract Background Cancer cachexia is a prevalent symptom of head and neck neoplasms. The reduction in skeletal muscle mass is one of the main characteristics which can lead to poor physical functioning. The purposes of this pilot randomized controlled trial were to determine the feasibility of progressive resistance training in cachectic head and neck cancer patients during radiotherapy and to explore possible risks and benefits. Methods Twenty cachectic participants with head and neck cancer receiving radiation were randomized to obtain either a machine supported progressive resistance training (n = 10) or usual care (n = 10). The training took place 3 times weekly for 30 min. Intervention included 3 exercises for major muscle groups with 8–12 repetition maximum for 3 sets each. Bioelectrical impedance analysis, hand-held dynamometry, Six-Minute Walk Test and standardized questionnaires for fatigue and quality of life were used for evaluating outcomes at baseline before radiotherapy (t1), after 7 weeks of radiotherapy (t2) and 8 weeks after the end of radiotherapy (t3). Results All participants (n = 20) completed the trial. No serious adverse events occurred. At the initial assessment the cachectic patients had already lost 7.1 ± 5.2% of their body weight. General fatigue (score 10.7 ± 3.3) and reduced quality of life (score 71.3 ± 20.6) were prevalent in cachectic head and neck cancer patients even before radiotherapy. An average improvement of weight loading for leg press (+ 19.0%), chest press (+ 29.8%) and latissimus pull-down (+ 22.8%) was possible in the intervention group. Participants had at least 13 training sessions. The outcome measures showed nonsignificant changes at t2 and t3, but a trend for a better course of general fatigue and quality of life at t2 in the intervention group. Conclusions Despite advanced tumor stage and burdensome treatment the intervention adherence is excellent. Progressive resistance training in cachectic head and neck cancer patients during radiotherapy seems to be safe and feasible and may have beneficial effects of general fatigue and quality of life. Trial registration ClinicalTrials.gov, NCT03524755. Registered 15 May 2018 - Retrospectively registered.